2019
DOI: 10.1021/acs.nanolett.9b01201
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Smooth Muscle Model Composed of Hierarchically Ordered Microtubule Asters Mediated by DNA Origami Nanostructures

Abstract: DNA has been well-known for its applications in programmable self-assembly of materials. Nonetheless, utility of DNA origami, which offers more opportunity to realize complicated operations, has been very limited. Here we report self-assembly of a biomolecular motor system, microtubule-kinesin mediated by DNA origami nanostructures. We demonstrate that a rodlike DNA origami motif facilitates self-assembly of microtubules into asters. A smooth-muscle like molecular contraction system has also been realized usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…We then begin the modeling study of the microtubule mesh structure using Blender to evaluate the characteristics of the dynamics and we explore possible ways to improve the target molecular system. Currently, we well reproduced contraction of this artificial muscle that is initiated upon ATP addition, as described in the previous report [ 4 ]. We will also discuss a potential strategy to accomplish multiple time contractions by a quick recovery method based on the obtained dynamic property of this contractile material.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…We then begin the modeling study of the microtubule mesh structure using Blender to evaluate the characteristics of the dynamics and we explore possible ways to improve the target molecular system. Currently, we well reproduced contraction of this artificial muscle that is initiated upon ATP addition, as described in the previous report [ 4 ]. We will also discuss a potential strategy to accomplish multiple time contractions by a quick recovery method based on the obtained dynamic property of this contractile material.…”
Section: Introductionmentioning
confidence: 65%
“…In nanotechnology, the mobile micromachine is gaining attention for potential application to the development of artificial muscle [ 1 , 2 , 3 ]. In particular, materials with microtubules and motor proteins have been demonstrated to provide contraction [ 4 ]. Motor proteins were designed to produce the pulling force between microtubule filaments that is known to happen in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted with permission from ref. [48].C opyright:2 019,American Chemical Society. case, GOx and HRP,w ith d-glucose as ar eactanta nd 3,3',5,5'tetramethylbenzidine as ar eporter) and then madet hese two nanotubes dimerise on their ends ( Figure 6B).…”
Section: Biomimetic Dna Nanotechnology For Potential In Vivo Applicatmentioning
confidence: 99%
“…Self-assembled MTs are attractive from a materials synthesis perspective, as MTs themselves are incredibly rigid, exceeding even single-walled carbon nanotubes in terms of their bending rigidity [14]. MTs have been considered for a wide range of applications, including tension sensors [15], lab-on-a-chip components [16], molecular robots, artificial muscles and others [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control the self-assembly and orientation of MTs is of paramount importance for future envisioned technologies including sensors, molecular motors and actuators, protein-based engineered nanostructures, etc. [14][15][16][17][18][19][20] Previous studies on MT polymerization, with or without PTX, mainly reported turbidity or absorbance as the primary means of evaluating their time-dependent bvpolymerization [42]. These techniques are attractive because they are simple and applicable to cell biology and cancer research, but they do not provide information regarding the micro-or macroscopic organization of MTs.…”
Section: Introductionmentioning
confidence: 99%